2013
DOI: 10.1155/2013/323868
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction Mechanism in Solid Polymer Electrolytes: New Concepts to Arrhenius Equation

Abstract: Solid polymer electrolytes based on chitosan NaCF 3 SO 3 have been prepared by the solution cast technique. X-ray diffraction shows that the crystalline phase of the pure chitosan membrane has been partially disrupted. The fourier transform infrared (FTIR) results reveal the complexation between the chitosan polymer and the sodium triflate (NaTf) salt. The dielectric constant and DC conductivity follow the same trend with NaTf salt concentration. The increase in dielectric constant at different temperatures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 39 publications
10
72
0
Order By: Relevance
“…It is obvious that at higher temperatures the DC conductivity increased rapidly as seen in Figure . This is due to the fact that at higher temperatures, movement of polymer chain segments is thermally enhanced . It would increase assisting and resulting in the increase in conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious that at higher temperatures the DC conductivity increased rapidly as seen in Figure . This is due to the fact that at higher temperatures, movement of polymer chain segments is thermally enhanced . It would increase assisting and resulting in the increase in conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…They calculated three values of E A from the slope of log σ −1000/ T for synthesized polymer blends and found the type of typical electronic conduction in between 0.456 and 0.712 eV for polymer blends while the values in excess of 0.8 eV are attributed to ionic conduction . Aziz et al . investigated to the electrical properties of solid polymer electrolyte based on chitosan:NaCF 3 SO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the band at 1379 cm -1 in the case of NR-CS (34 %) is seen to increase in comparison to that at 1456 cm -1 (in contrast to that in NR), and this may be due to the C-N stretching that could result due to the formation of C-N bonds between chitosan and ENR. Aziz and Abidin have earlier reported that the band position due to N-H stretching vibration could be significantly altered when a cation salt was attached to chitosan [34]. They also mentioned that in spite of the mixed signals arising from the N-H and O-H bond vibrations, the region starting from 3300 to 3500 cm -1 could be attributed to N-H vibrations.…”
Section: Resultsmentioning
confidence: 97%
“…B and C). To calculate activation energy ( E a ) at above mentioned temperature range, the well‐known Arrhenius equation is used : σdc=σ0e(Enormala/RT) where E a is the activation energy, R is universal gas constant, σ o is a temperature‐independent constant, and T is temperature (K). The plots showing a linear behavior between the Log σ or Log R and 1000/ T (K −1 ) indicated a good fit to the Arrhenius equation.…”
Section: Resultsmentioning
confidence: 99%